Keep Degrowth or go Rebirth? Regulatory focus theory and the support for a sustainable downscaling of production and consumption. (April 2021) - Krpan, Dario; Basso, Frédéric
Abstract: Considering that the growth model that dominates across the world is unsustainable, an increasing trend of publications indicates that transformative social change toward a "degrowth" economy is necessary to tackle climate change. Defined as an alternative sustainable social-economic model aiming for a downscaling of production and consumption, degrowth has been widely analyzed and documented in social and environmental sciences. However, despite this increasing academic interest, degrowth maintains a rather negative public perception, and remains under-researched in psychology. In a series of four online studies (N = 2408), collected in the US and UK, one of which was pre-registered and tested on a representative sample, our research investigated whether support for this alternative sustainable social-economic model could be influenced by its name labelling (Rebirth vs. Degrowth) and its definition framing (Promotion vs. Prevention), using the Regulatory Focus Theory. The main findings indicate that support for social change toward a degrowth economy increased when its definition was framed in terms of achieving positive consequences (Promotion) rather than avoiding negative consequences (Prevention), regardless of its name labelling. Overall, this article introduces the concept of degrowth to environmental psychology and in doing so hopes to inspire more psychological scientists to research this transformative social-economic model. Highlights: Degrowth is an alternative sustainable social-economic model. Using the Regulatory Focus Theory, we tested how to impact support for this model. Labelling degrowth as Rebirth (vs. Degrowth) did not reliably change its support. Defining degrowth in terms of Promotion (vs. Prevention) increased its support. This research introduces the concept of degrowth to environmental psychology.